Genomic Investigation of Salmonella Isolates Recovered From a Pig Slaughtering Process in Hangzhou, China - Wu, Beibei; Ed-Dra, Abdelaziz; Pan, Hang; Dong, Chenghang; Jia, Chenghao; Yue, Min (Frontiers in Microbiology, 2021)
Pigs’ industry was the principal source of meat products in China. However, the presence of pathogens in pig-borne meat is a crucial threat to public health. Salmonella was the major pathogen associated with pig-borne diseases. However, route surveillance by genomic platforms along the food chain was still limited in China. Here, we conducted a study to evaluate the dynamic prevalence of Salmonella in the pig slaughtering process in Hangzhou, Zhejiang province, China. 55 of 226 (24.37%) samples were positive for Salmonella, from them, 78 different isolates were selected and subjected to whole genomic sequencing following by bioinformatics analyses to evaluate the prediction serovars distribution, MLST patterns, antimicrobial resistance genes, plasmid replicons, and virulence factors. Moreover, phenotypic antimicrobial resistance was performed by broth dilution method against 14 antimicrobial agents belonging to 10 antimicrobial classes. Our results showed that samples collected from the dehairing area (66.66%) and splitting area (57.14%) were the most contaminated. Phenotypic antimicrobial resistance classified 67 of 78 isolates (85.90%) as multi-drug resistance (MDR), while the highest resistance was observed in tetracycline (85.90%; 67/78) followed by ampicillin (84.62%; 66/78), chloramphenicol (71.80%; 56/78), and Nalidixic acid (61.54%; 48/78). Additionally, serovars prediction showed the dominance of S. Typhimurium ST19 (51.28%; 40/78) among the 78 studied isolates while plasmids prediction reported the dominance of IncHI2A_1 (20.51%; 16/78), followed by IncX1_1 (17.95%; 14/78) and IncHI2_1 (11.54%; 9/78). Virulence factors prediction showed the detection of cdtB gene encoding typhoid toxins in two S. Goldcoast ST358 and one S. Typhimurium ST19 while one isolate of S. London ST155 was positive for genes encoding for the siderophore “yersiniabactin” and the gene senB encoding for enterotoxin production. From this study, we conclude that pig slaughterhouses are critical points for the dissemination of virulent and MDR resistant Salmonella isolates along the food chain which require the implementation of management systems to control the critical points. Moreover, there is an urgent need for the implementation of whole genome sequencing platform to monitor the emerging of virulent and MDR resistant clones along the food chain.